Peer Attachment and Academic Procrastination in Chinese College Students: A Moderated Mediation Model of Future Time Perspective and Grit - Jin, Hexiang; Wang, Wenchao; Lan, Xiaoyu (Frontiers in Psychology, 2019)
Although prior research has considerably documented the prevalence and correlates of academic procrastination in college students, relatively little is known about the role of longer volitional processes of goal striving, such as grit, on academic procrastination; moreover, the knowledge about direct and interactive effects of social context and personal characteristic on facilitating grit, which in turn mitigate academic procrastination, are still underexplored. Given these gaps in the existing literature, the current study, more exploratory in nature, investigates a moderated mediation model of future time perspective and grit in the association between peer attachment and academic procrastination in Chinese college students. A total of 1,098 undergraduate students (43.2% girls) aged from 18 to 25 were involved in the current study, and participants were asked to fill in a battery of self-report questionnaires. Results indicated that (a) peer attachment was negatively and significantly associated with academic procrastination; (b) grit partially mediated the association between peer attachment and academic procrastination; more precisely, peer attachment was positively associated with grit, which in turn was negatively linked to academic procrastination; and (c) future time perspective moderated the association between peer attachment and grit; more specifically, for students with low levels of future time perspective, the association between peer attachment and grit turned out to be significantly negative. These findings suggest that interventions targeting the enhancement of peer attachment and grit may prevent or reduce academic procrastination, and college students who regard future orientation as pessimistic should be paid specific attention by university-based counseling services.